2004
DOI: 10.21273/hortsci.39.7.1562
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence of Intra-cultivar Variability within Iberian Olive Cultivars

Abstract: A collection of 130 olive samples, originating from diverse areas in Europe and corresponding to 67 different cultivars denominations, was genotyped at 14 microsatellite loci. In total, 135 alleles with a mean number of 9.6 alleles per locus were detected. All but 30 accessions showed unique genotypes. Several cases of synonymy listed in the FAO database of olive germplasm could not be confirmed, as different allelic profiles were obtained from putatively synonymous cultivars. The existence of homonyms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
32
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 27 publications
(30 reference statements)
13
32
2
4
Order By: Relevance
“…In the present study, the different position of the cv. Galega in comparison to the other 28 cultivars, similar to that reported by other authors (Gemas et al 2004, Lopes et al 2004, suggest that it has a different origin. Moreover, Belaj et al (2002), studying 6 of these 29 Portuguese cultivars, found the same grouping among them as in the present work, and Galega also was independent.…”
Section: Resultssupporting
confidence: 88%
“…In the present study, the different position of the cv. Galega in comparison to the other 28 cultivars, similar to that reported by other authors (Gemas et al 2004, Lopes et al 2004, suggest that it has a different origin. Moreover, Belaj et al (2002), studying 6 of these 29 Portuguese cultivars, found the same grouping among them as in the present work, and Galega also was independent.…”
Section: Resultssupporting
confidence: 88%
“…SSR markers have been previously used in genetic diversity and relationship studies in olive cultivars, and most scientists conclude that SSR markers are a powerful tool for cultivar identification and analysis of genetic structure (Khadari et al 2003;Belaj et al 2003;Gomes et al 2009). Variations reported in the number of alleles in olive cultivars by different scientists may be related to variation in the loci studied as well as the number of genotypes and their localities (Lopes et al 2004) The dendrogram derived from UPGMA cluster analysis of the 32 SSR markers showed two main, distinct groups (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…At most, we have found a variant genotype at 2 SNP loci between trees of the same cultivar. The rate of intra-cultivar mutation calculated from microsatellites was much higher, ranging from a rate of 2 out of 30 loci in one study (Cipriani et al 2002) up to 15 % of the analyzed alleles in a second study (Lopes et al 2004). The SNP marker mutation rate is considerably lower than that of microsatellites (Kronholm et al 2010).…”
Section: Intra-cultivar Polymorphismmentioning
confidence: 85%